Platelet-Rich Plasma as Xenofree-Growth Factor For Mesenchymal Stem Cells Culture - Nurhidayati, Asti; Sukmawati, Dewi (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
Stem cell-based therapy is currently believed to be the future of medicine. The type of stem cell that is widely used in cell-based therapy is mesenchymal stem cells (MSCs). In stem cell-based therapy, the MSCs that will be used mostly need to be expanded first by culturing the cells. The serum that is often used in MSCs culturing is a fetal bovine serum (FBS). However, animal components should be avoided in clinical applications and Good Manufacturing Practices (GMP). FBS is not adhering to GMP, which compromises the safety and effectiveness of cell-based therapies. Therefore, other supplements are required for cultures without animal serum constituents. Platelet-rich plasma (PRP) is a plasma fraction derived from blood with a platelet concentration of 3-5 times higher than in blood. Several studies have shown that PRP contains various growth factors that can increase the proliferative and differentiation capacity of MSCs which is equivalent to or even better than FBS. PRP also has the advantage that it can be an autologous or allogeneic product from human peripheral blood, so it is free from animal substances. Therefore in the future PRP has great potential as an alternative to FBS both in culture expansion and in MSCs processing.